Electrical Power Analysis Using the Scattering Bond Graph - Roberto Tapia-Sánchez (Journal of Engineering)
The perspective of the well known concept of active and reactive power in electrical systems is addressed in this paper. This concept is presented from the point of view of the bond graph methodology. The scattering matrix concept is used in order to deal with these formulations. The concept of active and reactive power is presented with some examples derived from single-phase AC circuits. The formulations and simulations of these circuits are presented.